The Representation of Independence in the Japanese Original and Indonesian Translation of Madogiwa no Totto-chan - Ratna, Maharani Patria (Vocational College of Diponegoro University, 2026)
This study examines the representation of independence in the original Japanese novel Madogiwa no Totto-chan and its Indonesian translation. Data are collected from selected episodes in the original text and Indonesian translation that describe the social value of independence. Previous studies have discussed educational values and social values, but have not examined how independence shifts through domestication at the micro-narrative level. Using a qualitative descriptive approach and comparative text analysis, the study employs close reading techniques on the data by comparing the original Japanese text and the Indonesian translation. The main findings of this study indicate This study shows that the representation of independence in Madogiwa no Totto-chan undergoes a shift when translated into Indonesian. In general, Japanese text tends to frame independence as loose independence based on trust—characterized by spontaneous actions, markers of intensity, and leniency given by authority figures. In contrast, Indonesian text represents independence as a permitted and more orderly choice, so that the characters feel more normative under the supervision of authority figures.